2005
DOI: 10.1002/uog.1837
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the lung‐to‐head ratio in predicting outcome and neonatal ventilation parameters in fetuses with congenital diaphragmatic hernia

Abstract: Objectives The ratio of the lung area (on the contralateral side of the hernia) to the head circumference, the lungto-head ratio (LHR), has been proposed as a reliable tool in the assessment of the prognosis of congenital diaphragmatic hernia (CDH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 18 publications
(40 reference statements)
3
68
0
9
Order By: Relevance
“…Conversely, LHR did not differ significantly. LHR is reportedly useful for predicting subsequent survival (9), but some recent studies could not confirm the prognostic value of LHR for survival or the necessity of ECMO therapy (10,11). In general, ultrasonography has certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, LHR did not differ significantly. LHR is reportedly useful for predicting subsequent survival (9), but some recent studies could not confirm the prognostic value of LHR for survival or the necessity of ECMO therapy (10,11). In general, ultrasonography has certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, studies demonstrated a two to four fold increase in mortality among prenatally diagnosed CDH patients when compared with postnatally diagnosed patients (Skari et al, 2000). Although the reason behind this association is not clear, prenatal diagnosis of CDH may infer that the defect is larger with more displaced bowel and worse pulmonary hypoplasia (Laudy et al, 2003;Heling et al, 2005). Also, prenatal diagnosis has been associated with higher frequency of associated abnormalities, which may contribute to decreased survival of CDH children (Skari et al, 2002).…”
Section: Prenatal Identificationmentioning
confidence: 99%
“…The most commonly used method to assess fetal lung volume, and subsequent outcomes, is the measurement of lung area to head circumference ratio (LHR) with the use of 2-dimensional ultrasound (US) (Metkus et al, 1996;Sbragia et al, 2000;Laudy et al, 2003;Heling et al, 2005;Jani et al, 2006a;Hedrick et al, 2007;S.H. Yang et al, 2007;Sinha et al, 2009).…”
Section: Lung To Head Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“… calculation of the lung-to-heart ratio ( Fig. 1) as prognostic marker (Heling et al, 2005;Laudy et al, 2003;Lipshutz et al, 1997).  color flow Doppler for demonstrating abnormal position of umbilical and portal vein, identify right-sided hernias.…”
Section: Evaluation Strategies: Suggested Workup For Cdh Patientsmentioning
confidence: 99%